Penerapan Evidance Based Nursing Squeeze Ball Exercise terhadap Peningkatan Kekuatan Otot pada Pasien Stroke Non Hemoragik - Nur Laeli; Citra Setyo Dwi Andini; Endah Sari Purbaningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Nonhemorrhagic stroke is a disruption of blood flow to the brain due to blockage of blood vessels that has an impact on muscle weakness, impaired physical mobility, and limitations in daily activities. One of the nonpharmacological interventions that can be applied to improve upper extremity motor function is squeeze ball exercise. This study aims to describe the application of squeeze ball exercise in nonhemorrhagic stroke patients with physical mobility disorders in the stroke room. The research method is in the form of a descriptive case study with a nursing care approach in one patient. Data was collected through interviews, observations, physical examinations, documentation, and the application of squeeze ball exercises for four days with a duration of 5–10 minutes per session. Evaluation was carried out through observation of changes in the patient's muscle strength, grasping ability, and mobility. The results showed an increase in upper extremity muscle strength based on Manual Muscle Testing (MMT), from a scale of 2 to a scale of 4 after the intervention. The improvement was characterized by better grasping of rubber balls, more active hand movements, and increased patient independence in daily activities. During implementation, the patient shows a cooperative attitude and gradual motor improvement. This case study confirms that squeeze ball exercise can be used as a supportive therapy in the rehabilitation of nonhemorrhagic stroke patients because it contributes to increasing muscle strength, grasping ability, and physical mobility.